Estudo diacrônico das preposições com, em, por e per em textos portugueses do século XIV ao XX - Trujillo, Maria Francisca Ferreira (2012)
This research, imprint structuralist, entitled diachronic study of prepositions com, em, por and per, in Portuguese texts of the XIV to the XX century, aims to investigate and describe the prepositions com, em, por and per in the Portuguese language, spelling and its amendments senses under the historical perspective. It is historical and descriptive research that is based on analysis of historical grammars and texts from the fourteenth century to the twentieth. The corpus of archaic texts from fourteenth and fifteenth centuries, drawn from the collections of Jose J. Nunes (1959) and J. L. Vasconcellos (1959). The texts from the sixteenth to the eighteenth were consulted in the National Digital Library of Lisbon. To represent the nineteenth and twentieth centuries chose varied literary works of Brazilian writers, preferring prose and, as the literary genre, seeks to vary between tales, auto, novels etc., In order to diversify styles, while that were selected authors who represent a form as close to the standard level of language (the language with little spontaneous reproduction without regional variation, for this is not the object of our study). Initially are compared every two centuries between them, and finally, compares the data with the twentieth century, aiming to verify the occurrence of changes in spelling and meanings in these prepositional connectives. Anchored on the assumption that, on the basis of the linguistic system of Portuguese prepositional connectives occupy important role, justified the development of such a survey. As a result, it is believed that the prepositions themselves carry some degree of meaning that make them, in the Portuguese language, basic elements that accompany the diachrony of language without changing its form or function